Fertility in early breast cancer patients: integrating reproductive planning into oncology care - Turla, Antonella; Bellicini, Anna; Spada, Daniele; Mandruzzato, Marcella (Frontiers in Endocrinology, 2026)
Fertility preservation (FP) and adequate counseling are crucial for young breast cancer patients in the early setting. We provide a brief summary of FP in young breast cancer patients, including current international guidelines, available FP treatments, and the safety of pregnancy. This review explores embryo/oocyte cryopreservation, ovarian tissue cryopreservation (OTC), and gonadotropin-releasing hormone agonists (GnRHa), along with evidence on temporary endocrine therapy interruption to attempt pregnancy. Despite strong recommendations, FP uptake remains low, underscoring the need for timely multidisciplinary counseling. Literature data underline that pregnancy can be considered after treatment, even for hormone receptor-positive and BRCA mutation-positive patients. Reproductive planning should be integrated into the oncologic treatment, balancing oncologic priorities with patients’ reproductive desires.